MSMEs Financial Statements And The Factors Affecting Their Quality - Ratri Paramitalaksmi; Diana Airawaty (Cita Konsultindo Research Center, 2024)
The reason of this investigate is to discover the affect of entrepreneurs' discernments on the quality of MSME financial statement moderated by self-efficacy, the impact of bookkeeping understanding on the quality of MSME financial statement moderated by self-efficacy, the impact of MSME digitalization on the quality of MSME financial statement moderated by self-efficacy. The populace in this think about is MSMEs in Banguntapan Area, Bantul, Yogyakarta. The information utilized is essential information. Essential information is within the shape of survey comes about and in-depth interviews with MSME business people in Banguntapan Area, Bantul, Yogyakarta. Information handling in this think about utilized Smart PLS. The result of this think about is that indeed without self-efficacy, the discernment of trade on-screen characters and digitalization of MSMEs in Banguntapan Area influence the quality of MSME money related explanations based on SAK EMKM. Then again, the level of bookkeeping understanding had by each MSME on-screen character in Banguntapan Area does not influence the quality of monetary explanations indeed with self-efficacy.